Short-term consequences of Helicobacter pylori treatment in patients with oral lichen planus: A prospective study - Farshad Javadzadeh; Masoud Shirmohamadi; Maryam Hosseinpour Sarmadi; Morteza Ghojazadeh; Sepideh Bohlouli; Amir Ghorbanihaghjo; Solmaz Pourzare (Journal of Advanced Periodontology and Implant Dentistry)
Background. Oral lichen planus (OLP) is a multifactorial chronic inflammatory condition with unknown etiology. This condition has been associated with Helicobacter pylori. This study aimed to investigate the relationship between the treatment of H. pylori infection and improvements in OLP lesions. Methods. In this cohort study, 42 patients with erosive or ulcerative OLP lesions were evaluated in terms of H. pylori infection using the H. pylori stool antigen (HpSA) test. The patients were divided into three groups. The first group consisted of 12 H. pylori-negative patients. The second group consisted of 21 H. pylori-positive patients receiving antibacterial treatment. The third group included nine H. pylori-positive patients not willing to receive treatment. All the three groups underwent the usual OLP treatment. Patients in the second and third groups were re-evaluated by the HpSA test after two months. The efficacy indexes and visual analog scale were used to evaluate clinical improvements. Results. The efficiency index and pain scores were affected by the intervention (P<0.001). The logistic regression analysis showed that the severity index before treatment was significantly effective (OR=0.745 (95% CI: 0.602‒0.923; P=0.007). No statistical significance for factors affecting other variables (P>0.05) was obtained. Conclusion. Pain intensity was higher in patients with H. pylori than in those without H. pylori before treatment. Also, in patients with H. pylori, the treatment affects the complete recovery rate.